2012
DOI: 10.1007/s10823-012-9167-0
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Contextual Analysis of Quality of Life Among Older Nepali Women

Abstract: The quality-of-life construct can be used to assess how well an individual's needs are met or being met by the society. However, in the dominant narratives of quality of life in old age, exploration of the impact of cultural differences on how older adults define and assess their quality of life has been limited. Moreover, the examination of heterogeneity within one culture and its influence on quality of life has been largely ignored. The present study compares the quality of life as defined by two samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…28,35 This is probably because of social, cultural, educational and economic difference that affects nutritional status of individuals. [35][36][37] Similarly, the other related studies also suggested that the prolonged stay in the institutions (geriatric rehabilitation center, old age care homes or hospitals) led to poorer nutritional status which is also similar to the findings of this study. 13,38,39 Therefore the screening and regular nutrition examinations are essential, since large number of malnourished individuals are unrecognized and untreated at old age homes.…”
Section: 27supporting
confidence: 89%
“…28,35 This is probably because of social, cultural, educational and economic difference that affects nutritional status of individuals. [35][36][37] Similarly, the other related studies also suggested that the prolonged stay in the institutions (geriatric rehabilitation center, old age care homes or hospitals) led to poorer nutritional status which is also similar to the findings of this study. 13,38,39 Therefore the screening and regular nutrition examinations are essential, since large number of malnourished individuals are unrecognized and untreated at old age homes.…”
Section: 27supporting
confidence: 89%
“…This finding does not indicate a higher level of ageism in the less-developed countries than the more-developed countries. In fact, among the less-developed countries, such as Nepal, there are often cultural traditions that promote positive-aging views [114]. The greater proportion of significant ageism-health associations in less-developed countries may, instead, be explained by their tending to have fewer resources to provide health care to older persons, compared to more-developed countries [115].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative methods were used to explore the behaviours, meanings, perceptions, and experiences of the residents within the context of their culture and with regard to health (14). An approach embracing culture as a constitutive space and including the researcher’s role as a listener of the marginalized within their micro-context guided the study (1115).…”
Section: Methodsmentioning
confidence: 99%
“…Specific public health goals related to promoting good health within a community have not been consistently defined in Nepal, and there have been no apparent published investigations about health needs from the residents’ perspectives in a rural area, particularly among these under-resourced rural women. In a review of the published literature, one study was found that documented the meaning of reproductive health among young Nepalese women in poverty and focused on safe motherhood (11), and other researchers investigated the quality of life among Nepalese women refugees (12). The majority of Nepal’s residents live in rural areas, comprising 82.0% of the general population in 2013 (13).…”
Section: Introductionmentioning
confidence: 99%